Analyzing Flooding Impacts on Rural Access to Hospitals and Other Critical Services in Rural Cambodia Using Geo-Spatial Information and Network Analysis - Espinet Alegre, Xavier; Stanton-Geddes, Zuzana; Aliyev, Sadig; Bun, Veasna (World Bank, Washington, DC, 2020)
Transport connectivity in Cambodia is challenged by its geography and exposure to recurrent flooding. Flood events create severe disruptions in segments of the transport network that undermine access to health, education, and work opportunities as well as create barriers to economic growth. Rural accessibility to emergency health facilities and delivery of medicines and basic food supplies is particularly critical in times of major health crises, such as the ongoing COVID-19 outbreak. This paper provides a method to quantify the impact of flooding on hospital access and other critical facilities, aiming to support governments on setting up health emergency mitigation plans for rural transport in an environment with high flood risk. The method was piloted in three provinces in rural Cambodia, estimating that for 37 percent of the people on those provinces, it takes more than 60 minutes to reach an emergency health facility. During floods, 27 percent lose all access and 18 percent experience an increase of 30 minutes in travel time. In conclusion, this method introduces transparency and evidence-based support for prioritization of rural transport investment, identifies the social benefits (health and education) of rural infrastructure investments, and supports policy dialogue on rural development and resilience.